Addressing Gaps in Sustainable Hazardous Waste Management in MSMEs: A Case Study of Motorcycle Repair Shops - Iriany, Milda Restuti; Sodri, Ahyahudin; Agustina, Haruki (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Motorcycle repair shops on the MSME (micro, small, and medium enterprise) scale continue to grow and become an important sector in people's lives. Vehicle maintenance activities in repair shops generate hazardous waste, which needs to be further managed and encouraged to achieve sustainable management. This article analyzes gaps in managing hazardous waste from MSME repair shops in achieving sustainability. This research collected data from 95 repair shop respondents in East Jakarta City, Indonesia. As a complement, the role of hazardous waste management service businesses in managing waste from motorcycle repair shops is also examined based on current management. The collected data was then analyzed descriptively. The research results found that there are gaps that need to be addressed in achieving sustainability, namely the gap in knowledge and attitudes, the gap in behavior (implementation of hazardous waste management), and the gap in the economic value of waste. There is a need for increased knowledge, guidance, and supervision, adjustments to hazardous waste management policies, and the selection of profitable economic instruments. This study is expected to provide input on implementing sustainable hazardous waste management in businesses at the MSME level in Indonesia.